2009
DOI: 10.1111/j.1365-2265.2008.03502.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations and tissue expression of a novel endocrine regulator fibroblast growth factor‐21 in patients with type 2 diabetes and obesity

Abstract: An increase in FGF21 levels after VLCD and fenofibrate treatment may contribute to positive metabolic effect of these interventions and suggests the possibility of direct positive metabolic effects of FGF21 in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
209
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(234 citation statements)
references
References 28 publications
17
209
7
1
Order By: Relevance
“…Furthermore, our results indicate that adipose tissue is the main source of circulating FGF21 in obese women. This hypothesis is confirmed by the observation of an increase in FGF21 expression in visceral fat in obese subjects (20). It should be emphasised that the stronger association between FGF21 and HOMA-IR values than fat mass and waist circumference implies that higher FGF21 production and secretion may be an inefficient contraregulatory mechanism preventing insulin resistance development in obese subjects.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, our results indicate that adipose tissue is the main source of circulating FGF21 in obese women. This hypothesis is confirmed by the observation of an increase in FGF21 expression in visceral fat in obese subjects (20). It should be emphasised that the stronger association between FGF21 and HOMA-IR values than fat mass and waist circumference implies that higher FGF21 production and secretion may be an inefficient contraregulatory mechanism preventing insulin resistance development in obese subjects.…”
Section: Discussionsupporting
confidence: 71%
“…Results including decrease (18), no change (19) and increase (20) were all described. However, it should be noted that an increase in FGF21 levels was observed in patients when combined with very-low-calorie diet (VLCD) and fenofibrate therapy (20). The results of study in monozygotic and dizygotic young adult twins revealed that genetic factors moderately contributed to circulating FGF21 variability (21).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that fasting and feeding may regulate FGF21 expression (Uebanso et al, 2011). This factor may be a risk factor for some diseases like insulin resistance, type 2 diabetes mellitus and metabolic syndrome (Mraz et al, 2009;Bobbert et al, 2013). Some studies have revealed that serum FGF21 influenced by high blood glucose, increased body mass index, uric acid level and low physical activity (Cuevas-Ramos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been predominantly investigated in the liver and adipose tissue [10]. However, FGF21 is also expressed in other tissues such as the myocardium [11].…”
Section: Introductionmentioning
confidence: 99%